Self‐commissioning of flux linkage curves of synchronous reluctance machines in quasi‐standstill condition. Issue 9 (1st November 2015) - Peretti, Luca; Sandulescu, Paul; Zanuso, Giovanni
Abstract : This study presents a self‐commissioning procedure for the estimation of the flux linkage curves of synchronous reluctance machines. The procedure exploits a quasi‐standstill condition obtained by imposing fast torque oscillations. The flux linkage is calculated by means of a pure integration of the voltages and currents. With respect to the existing procedures, the proposed one tackles the problem of the limited knowledge of the core losses in the electrical machine, which is shown to induce erroneous estimation results for the case under investigation. A theoretical analysis supported by extensive laboratory measurements is shown, proving the effectiveness of the proposed approach.